2022
DOI: 10.1128/spectrum.00414-22
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Microbiome Analysis via Noninvasive Prenatal Testing Reveals the Complexity of Circulating Microbial Cell-Free DNA

Abstract: While circulating cell-free DNA (cfDNA) has been becoming a powerful marker for noninvasive identification of infectious pathogens in liquid biopsy specimens, a baseline for microbial cfDNA in healthy individuals is urgently needed for the proper interpretation of microbial cfDNA sequencing results in clinical metagenomics. Standard low-pass whole-genome-sequencing-based NIPT shares many similarities with the sequencing protocol for metagenomics and could provide a microbial cfDNA baseline in healthy people; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
1
9
0
3
Order By: Relevance
“…Leveraging the concept of the multibiome, which delineates the interaction between different microbial entities (i.e., bacteria, fungi and viruses) as a community, a recent study revealed fascinating links between signatures of the blood microbiome and pathogens known to inflict pregnancy-related complications, namely Toxoplasma gondii , Hepatitis B virus, Human Papillomavirus (HPV), Rubella virus, Cytomegalovirus and Herpes simplex virus (HSV) [ 67 ]. For example, HPV positive blood samples were linked to elevated Weissella paramesenteroides and Propionibacterium acne, while blood samples positive for HSV had higher abundance of Bifidobacterium bifidum and Propionibacterium acne [ 67 ]. Toxoplasma gondii also has a high tendency to co-occur with Pectobacterium carotovorum and Chthoniobacter flavus in blood [ 67 ].…”
Section: Clinical Significance Of the Blood Microbiome In Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leveraging the concept of the multibiome, which delineates the interaction between different microbial entities (i.e., bacteria, fungi and viruses) as a community, a recent study revealed fascinating links between signatures of the blood microbiome and pathogens known to inflict pregnancy-related complications, namely Toxoplasma gondii , Hepatitis B virus, Human Papillomavirus (HPV), Rubella virus, Cytomegalovirus and Herpes simplex virus (HSV) [ 67 ]. For example, HPV positive blood samples were linked to elevated Weissella paramesenteroides and Propionibacterium acne, while blood samples positive for HSV had higher abundance of Bifidobacterium bifidum and Propionibacterium acne [ 67 ]. Toxoplasma gondii also has a high tendency to co-occur with Pectobacterium carotovorum and Chthoniobacter flavus in blood [ 67 ].…”
Section: Clinical Significance Of the Blood Microbiome In Human Diseasesmentioning
confidence: 99%
“…For example, HPV positive blood samples were linked to elevated Weissella paramesenteroides and Propionibacterium acne, while blood samples positive for HSV had higher abundance of Bifidobacterium bifidum and Propionibacterium acne [ 67 ]. Toxoplasma gondii also has a high tendency to co-occur with Pectobacterium carotovorum and Chthoniobacter flavus in blood [ 67 ]. Essentially, the variations in the blood microbiome and co-occurrence of harmful pathogens with other microbes could be invaluable for the development of newer stratification strategy to identify mothers with a high risk for pregnancy-related complications via non-invasive maternal blood analysis.…”
Section: Clinical Significance Of the Blood Microbiome In Human Diseasesmentioning
confidence: 99%
“…Однако эти данные зачастую противоречивы, их недостаточно для использования в клинической практике, поэтому необходимы дальнейшие исследования. Следует отметить, что вкДНК также содержит митохондриальную ДНК (вкмтДНК), фрагменты геномов вирусов и бактерий [9][10][11]. Повышение уровня митохондриальной ДНК (мтДНК) в крови обнаружено у женщин c преэклампсией [12][13][14][15][16][17], гестационным сахарным диабетом [18], задержкой развития плода [19].…”
Section: Key Messages What Is Already Known About the Subject?unclassified
“…Это позволяет рассматривать вкмтДНК в качестве потенциального биомаркера осложнений беременности. В свою очередь вирусные и бактериальные инфекции также могут вызвать осложнения беременности, а их своевременное выявление и лечение позволяет избежать тяжелых последствий [9,11,20].…”
Section: Key Messages What Is Already Known About the Subject?unclassified
See 1 more Smart Citation